Rumours of Wars and Deeds of Emperors: Circulation of News and "Stories" about Non-Venetians in Early Medieval Venice. Issue 2 (3rd May 2016) - Berto, Luigi Andrea
ABSTRACT: Venice's geographic position firmly places it in Western Europe, yet its history demonstrates that Venice had many ties and interests in the eastern Mediterranean. Initially on the Byzantine periphery, Venice became an autonomous duchy during the eighth century, but continued to nurture close relations with the Byzantines and intensified those with the rest of Europe. Moreover, the economic and other activities of its inhabitants enabled a widespread Venetian presence in the Mediterranean world and some parts of Europe. At the same time, foreigners were drawn to this network of lagoons and islands. Taking advantage of these factors, this article aims to examine the circulation of news and descriptions of events concerning "others" in early Medieval Venice.